Thermostable Chitosan-L-Asparaginase conjugate from Aspergillus fumigatus is a novel structurally stable composite for abolishing acrylamide formation in French fried potatoes. (1st June 2022) - Yassin, Marwa A.; Shindia, Ahmed; Labib, Mai; Soud, Mohamed; El-Sayed, Ashraf S.A.
Abstract: l -Asparaginase (Asnase) is one of the most promising approaches for acrylamide mitigation in foods, however, the enzyme stability and catalytic efficiency are the major challenges. Thus, purification of highly active thermostable Asnase from fungi and increasing its structural stability for acrylamide reduction via conjugation with biocompatible polymers was the objective of this study. The highest enzymatic yield was obtained from Aspergillus fumigatus MW737636.1 (Af-Asnase) grown at 40 °C, with 2.3 folds increments by bioprocessing with Plackett-Burman design. The enzyme was purified by 2.8 folds, with 50 and 200 kDa by denaturing and native-PAGE, i.e homotetrameric identity. The enzyme was immobilized on dextran and chitosan with yield ∼68%, as validated from the FT-IR analyses, ensuring the formation of covalent C–N bonds of enzyme with the polymers. The proteolytic resistance stability of Af-Asnase was strongly increased upon conjugation with dextran and chitosan, ensuring the shielding of surface recognition sites by 50–70%. The highest enzymatic activity was reported at 40 °C with maximum affinity for l -asparagine. Chitosan-Af-Asnase conjugates exhibit a dramatic structural stability and efficiency for abolishing the acrylamide formation in French fried potatoes comparing to free l -asparaginase. The conformational stability and catalytic efficiency of chitosan Af-Asnase has been resolved from the molecular modeling and docking analysis. Highlights: Chitosan and dextran-Asnase have a strong structural stability against proteolysis. The catalytic efficiency of chitosan-Asnase was increased by 2 folds than the free one. Chitosan-Asnase eliminates the acrylamide in pretreated French fried Potatoes.